Nuclear magnetic resonance as an analytical tool for monitoring the quality and authenticity of dairy foods. (February 2021) - Balthazar, Celso F.; Guimarães, Jonas T.; Rocha, Ramon S.; Pimentel, Tatiana C.; Neto, Roberto P.C.; Tavares, Maria Inês B.; Graça, Juliana S.; Alves Filho, Elenilson G.; Freitas, Mônica Q.; Esmerino, Erick A.; Granato, Daniel; Rodrigues, Sueli; et al.
Abstract: Background: In the last years, consumers are more conscious about nutrition, welfare, authenticity, and quality of dairy products. Nuclear magnetic resonance (NMR) technology has gained attention as a potential method for food quality and authenticity purposes. Scope and approach: This review aimed to comprehensively explain and discuss the use of NMR for quality and authenticity of milk and dairy products. Key findings and conclusions: The NMR technology showed to be an effective tool to ensure the authenticity and to control the quality of dairy products during the processing and storage. It may be used to measure the fat content of milk and dairy products, evaluate the geographic origin, the molecular water mobility and the water retention capacity of cheeses, study the water mobility in milk beverages, and quantify the bound water molecules in ice creams. Additionally, NMR can detect whey, urea, hydrogen peroxide, synthetic urine, and synthetic milk in raw milk. Furthermore, it can evaluate physicochemical and sensory parameters of the products. NMR is a non-destructive technique, no need sample preparation or solvent separation, is fast and simple, and has high instrumental stability. However, it has disadvantages, like the high costs of acquisition and maintenance. The characterization of dairy foods may benefit from the combination of NMR and chemometrics, mainly to deal with large data matrices and highlight differences/similarities among samples. Graphical abstract: Image 1 Highlights: Nuclear magnetic resonance for dairy foods. Theory aspects of Nuclear magnetic resonance are presented. Nuclear magnetic resonance can be used to detect fraud in dairy products. Nuclear magnetic resonance is adequate for monitoring quality aspects in dairy foods processing.